Ultrasensitive bioanalysis: current status and future trends. (May 2017) - Simon, Stéphanie; Ezan, Eric
Ligand-binding techniques such as immunoassays, the reference for clinical diagnosis, offer a wide range of innovative approaches based on signal DNA amplification, nanotechnologies or digital assays, which result in technologies with sensitivities more than 1000-times that of formats used 20 years ago. Providing that these technologies gain acceptance and translate into robust commercial platforms, we expect that several fields will be impacted in the near future, including the clinical diagnosis of cancer markers, the early detection of infectious diseases and the safety of biotherapeutics. Furthermore, the combination of these techniques with microfluidic systems will allow probing of biological diversity at the single cell level and will lead to the discovery of novel and rare biomarkers.